Ratio Decidendi of Restitution Imposition in Juvenile Crimes from a Restorative Justice Perspective - Burhanuddin Mohammad; Syamsuddin Syamsuddin; Hajairin Hajairin (Bulletin of Community Engagement, 2026)
Restitution as a mechanism for restoring the rights of victims in juvenile criminal justice systems has garnered significant scholarly attention, yet its application in Indonesian legal practice remains inconsistent and theoretically underdeveloped. This study examines the ratio decidendi underlying judicial decisions that impose restitution in juvenile criminal cases, critically analyzed through the lens of restorative justice theory. Employing a normative juridical methodology complemented by a comparative approach, this research systematically analyzes a corpus of judicial decisions from Indonesian courts, relevant statutory frameworks, and international human rights instruments pertaining to child victims of crime. The findings reveal that Indonesian courts have yet to establish a coherent and uniform ratio decidendi in imposing restitution upon juvenile offenders; judicial reasoning is frequently characterized by discretionary and inconsistent application of legal principles, inadequate balancing of the punitive and rehabilitative imperatives, and insufficient consideration of the victim-centered dimensions of restorative justice. This study further demonstrates that the extant legislative architecture most notably Law Number 11 of 2012 on the Juvenile Criminal Justice System provides an enabling normative foundation for restorative-based restitution, yet systemic implementation gaps persist due to the absence of structured judicial guidelines, limited prosecutorial capacity, and underdeveloped victim support infrastructure. This article contributes to the academic discourse by formulating a comprehensive ratio decidendi framework specifically tailored for restitution in juvenile cases, integrating the principles of proportionality, rehabilitation, reparation, and victim participation. The study concludes with policy recommendations directed at legislators, the Supreme Court of Indonesia, and law enforcement institutions to strengthen the normative and practical framework for restorative restitution in the Indonesian juvenile justice system.